The role of religion in alcohol consumption and demand reduction in Muslim majority countries (MMC). (11th March 2016) - Kalema, David; Vanderplasschen, Wouter; Vindevogel, Sofie; Derluyn, Ilse
Abstract : Commentary to:Extent of alcohol prohibition in civil policy in Muslim majority countries: the impact of globalization